2021
DOI: 10.1007/s10334-021-00911-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping tumour heterogeneity with pulsed 3D CEST MRI in non-enhancing glioma at 3 T

Abstract: Objective Amide proton transfer (APT) weighted chemical exchange saturation transfer (CEST) imaging is increasingly used to investigate high-grade, enhancing brain tumours. Non-enhancing glioma is currently less studied, but shows heterogeneous pathophysiology with subtypes having equally poor prognosis as enhancing glioma. Here, we investigate the use of CEST MRI to best differentiate non-enhancing glioma from healthy tissue and image tumour heterogeneity. Materials &a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 31 publications
(50 reference statements)
1
29
0
Order By: Relevance
“…To evaluate the extent of hyper/hypointensity of LD APT/ NOE and MTR REX APT/NOE within the tumor per patient, a patient-specific threshold was determined as reported in [17] (3)…”
Section: And 4 Based On Ldmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the extent of hyper/hypointensity of LD APT/ NOE and MTR REX APT/NOE within the tumor per patient, a patient-specific threshold was determined as reported in [17] (3)…”
Section: And 4 Based On Ldmentioning
confidence: 99%
“…In addition, MTR asym cannot evaluate saturation pools on opposite sides of the main resonance frequency individually, i.e., the effect of APT (3.5 ppm) and nuclear Overhauser enhancement (NOE, at − 3.5 ppm) are both reflected in MTR asym at 3.5 ppm. Advanced metrics were proposed for separation of the APT and NOE signal, via multi-pool Lorentzian fitting [28] and the isolation of individual CEST effects by the Lorentzian difference (LD) [17,[28][29][30][31][32][33]. In addition, relaxation-compensated inverse magnetization transfer ratio (MTR Rex [34,35]) combined with Lorentzian fitting was proposed in glioma imaging at clinical field strength (3 T) to account for spillover effects that cannot be compensated by LD analysis [13,28,30,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In human patients, hyperintensities of APTw were found in tumors when compared with the contralateral regions [11,23,25,26,33,36,39,[42][43][44]60,70,[87][88][89][90][91][92] (Table 1). These increased APTw signals were positively correlated to high cellularity [39,70] and were validated by histology.…”
Section: Apt-weighted (Aptw) Contrastmentioning
confidence: 99%
“…In general, NOE signals consistently decrease among different analyses in both human and animal studies. Among these studies, there is one study that showed unchanged NOE in a non-enhancing glioma, while APTw signal consistently increased in both enhancing and non-enhancing gliomas [11]. Nevertheless, NOE could be an additional CEST contrast to indicate molecular changes in brain tumors.…”
Section: Noe Contrastmentioning
confidence: 99%
“…In the case of glioma imaging, amide proton transfer (APT) CEST is the most common application of CEST, although not as widely available or commonly used as MRS. Elevated concentrations of proteins in glioma compared to surrounding tissues and the high rates of intracellular proton exchanges leads to an increased APT level. APT CEST can be used to differentiate between LGGs and HGGs ( Choi et al, 2017 ), differentiation between regions of tumor and peritumoral edema ( Wen et al, 2010 ), and is gaining interest as a method of investigating intratumoral heterogeneity ( Warnert et al, 2021 ). One notable advantage of MRS over CEST is that MRS is able to simultaneously quantify multiple compounds, while CEST is only able to acquire one or two compounds at a time.…”
Section: Preoperative Imaging and Surgical Planningmentioning
confidence: 99%